Assessing the spatiotemporal variation in anthropogenic heat and its impact on the surface thermal environment over global land areas. (December 2020) - Jin, Kai; Wang, Fei; Wang, Shaoxia
Highlights: Impact of anthropogenic heat on the surface heat environment over the entire planet was explored at different spatial scales. Among six global sub-regions, Asia Pacific showed the largest anthropogenic heat in 2018 (0.29 W/m 2 ). The averaged terrestrial AHFs were generally comparable to the corresponding SNSRs in urban areas. A significantly positive correlation between AHF and ESUHI was found in eastern China where undergone rapid urbanization in the past four decades. Abstract: Anthropogenic heat that is mainly released in cities is rapidly rising in the context of global warming, while its impact on the land surface thermal environment is not completely clear. This study compared the anthropogenic heat flux (AHF) with the surface net solar radiation (SNSR) and analyzed the relationship between AHF and the surface urban heat island effect (ESUHI ) on the basis of the estimation and analysis of global terrestrial AHF. Results indicated that the global-averaged terrestrial AHF caused by energy consumption and human metabolism increased from 0.07 to 0.15 W/m 2 from 1980 to 2018. While a decrease in AHF mainly occurred in the developed cities of Europe and the United States, developing cities, particularly in eastern China, experienced an increase in AHF. The averaged terrestrial AHFs were far less than the corresponding SNSRs at the global and continental scales, whereas they were generally comparable in urban areas. AHF in the 100 largest cities around the globe was 19.56 (6.54) W/m 2 in 2018 (1980) on average, which was approximately 12% (4%) of the corresponding SNSR. Additionally, we found a significantly positive correlation between AHF and ESUHI in eastern China ( R 2  = 0.8383, P < 0.01). These findings imply that anthropogenic heat has a considerable impact on the land surface thermal environment and is one of the most important contributors to dramatic urban warming, which needs to be considered in future climate-related policy formulation and evaluation.